2022
DOI: 10.1186/s12884-022-04824-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of efforts to prevent maternal deaths due to obstetric hemorrhage on trends in epidemiology and management of severe postpartum hemorrhage in Japan: a nationwide retrospective study

Abstract: Background The Japan Society of Obstetrics and Gynecology and the Japan Association of Obstetricians and Gynecologists have issued the guidelines and recommendations on postpartum hemorrhage since 2010 and have been conducted widespread educational activities from 2012. The aim of this study was to investigate the impact of these efforts by the Societies to prevent maternal deaths due to obstetric hemorrhage on trends in epidemiology and management of severe postpartum hemorrhage in Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the study setting was a referral hospital, where more complicated pregnancies were admitted from rural health centers of the catchment area. A recent nationwide retrospective study done in Japan also showed that cases of PPH managed in large referral hospitals increased over time 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study setting was a referral hospital, where more complicated pregnancies were admitted from rural health centers of the catchment area. A recent nationwide retrospective study done in Japan also showed that cases of PPH managed in large referral hospitals increased over time 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of emergency hysterectomy among PPH cases ≥1,500 mL (0.079) were obtained from the statistics of emergency hysterectomy and massive PPH in Hong Kong public hospitals [ 6 ]. The mortality of hysterectomy for severe PPH were approximated using the national registry findings on hysterectomy and maternal mortality of patients with severe PPH in Japan [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Placental abruption is a life‐threatening obstetrical emergency that influences maternal and neonatal morbidity and mortality. It is defined as the complete or partial premature separation of the placenta from the uterine wall before delivery and has been estimated to occur in 0.3%–1.0% of all pregnancies 1–3 . Various risk factors of placental abruption have been reported thus far, including advanced maternal age, cigarette smoking, maternal hypertension such as preeclampsia, premature rupture of membranes, chorioamnionitis, and oligohydramnios 4 …”
Section: Introductionmentioning
confidence: 99%
“…It is defined as the complete or partial premature separation of the placenta from the uterine wall before delivery and has been estimated to occur in 0.3%-1.0% of all pregnancies. [1][2][3] Various risk factors of placental abruption have been reported thus far, including advanced maternal age, cigarette smoking, maternal hypertension such as preeclampsia, premature rupture of membranes, chorioamnionitis, and oligohydramnios. 4 At present, there are no established methods of predicting or preventing placental abruption, thus probably the only effective solution to improve neonatal hypoxic-ischemic morbidity and mortality is early intervention for that pregnancy, namely, the prompt clinical diagnosis of placental abruption and emergency cesarean section.…”
Section: Introductionmentioning
confidence: 99%